Comparison of Oxidative Stress Effects on Enzymatic and Non-Enzymatic Indices in Patients with Mild and Severe Obstructive Sleep Apnea - Parichehr Hanachi; Zahra Ghaseminya; Khosro Sadeghniyat; Abolfazl Golestani (Tehran University of Medical Sciences, 2018)
Background and Aim: Obstructive sleep apnea (OSA) is one of the most common sleep disorders that, despite the high prevalence, most people are unaware of it. The reason for this disorder is obstruction of the respiratory tract, which reduces blood oxygen as a result of frequent waking during the night. In this study, the status of antioxidant defense was considered as one of the most important mechanisms involved in preventing the consequences of this complication. Materials and Methods: The 35 subjects of OSA were selected and categorized according to the apnea-hypopnea index (AHI) in two groups: Mild OSA (n=17) and severe OSA (n=18). The fasting blood samples were taken in order to evaluate the antioxidant defense status of the glutathione peroxidase activity (GPx) and glutathione (GSH) content. Results: The results showed the mean values for GPx in patients with mild and severe apnea were 36.6±2.2 and 35.3±3.7 (u/gHb), respectively. Also, the mean values for GSH content in patients with mild and severe apnea were 0.54±0.1 and 0.68±0.1 µM, respectively that showed a 23% increase (P˂0.05) in severe apnea patients. Conclusion: There was no significant difference in the GPx activity of mild apnea, however, patients with severe apnea showed a significant increase in GSH levels compared to mild apnea (P<0.05), which may indicate a long-term response to oxidative stress alters gene expression and increases the level of these biomarkers in a long time.